Propuesta técnica para el cierre del relleno sanitario municipal del cantón Pastaza - Gaibor Rivera, Karen Estefania (2017)
The municipal solid waste landfill cell in the Pastaza city receives a daily amount of 43 tons of waste, as a result of a per capita production of 0.69 kg p per day each person. The cell was opened in 2010, and designed for an estimated operational time of 15 years. However, due to an inefficient management, the cell is currently in its closure stage. The aim of this study is to find a viable solution to this problem by designing a technical proposal for the closure, which will allow to maintain the operations in accordance to the environmental standards. First, we performed a situational diagnosis of the current state of the landfill to identify weaknesses in solid waste management, then we propose a closure plan divided in two phases: Phase one to improve the conditions of waste degradation in order to reduce the current height of 7 meters to 3 meters, and Phase two for the definitive closure of the cell which includes: the adaptation of terraces and vegetation cover, control of mounds, and improvements in the leachate treatment plant. This study aims to recover the original conditions of the landscape and control the pollution generated during the period of closure.